CONTRIBUTION OF MOTION STUDY TO STANDARD TIME AT BALL TEA STATION (CASE STUDY PT. MITRA KERINCI, SOUTH SOLOK) - Aldino Rizki Prayoga; Meizul Zuki; Yusril Dany (BPFP Faperta UNIB, 2021)
PT Mitra Kerinci is a company established in West Sumatra Province which is engaged in tea plantations and tea processing in its factories. PT Mitra Kerinci produces an average of 7,000 kg or 7 tons of green tea shoots per day. The production process for processing tea shoots, the factory sometimes does not reach the production target in accordance with the production target of the company. The goal of research to determine the amount of the contribution of the motion study to the standard time and determine the amount of the contribution of the standard time to the increase in productivity in the final drying process at Ball Tea station, the production of tea shoots at PT. Kerinci Partners. This research an experimental research type and uses the same subject research design (treatment by subject design), namely the treatment is imposed on the same subject. The results of time calculations after the motion study on the process flow map reached 15,676.02 seconds. Then proceed with the calculation of the cycle time which reaches 825.41 seconds with the actual standard deviation obtained at 3.58 and the standard deviation of the subgroup distribution is 1.79. After knowing the results of the average cycle time, the actual standard deviation and the standard deviation of the subgroup distribution, the data uniformity test was continued, starting with calculating the BKA and BKB. The BKA calculation results obtained 830.78 and the BKB reached 820.04. So that in the data uniformity test the results reached 0.908. In the series of movements of the left and right hands after the repair, a cycle time of 825.41 seconds / unit of Ball Tea was obtained from the previous time, reaching 906.66 units / Ball Tea and getting a time difference of 81.25 seconds. In the calculation of the standard time, the normal time calculation is carried out first, after it is known that the result of the adjustment calculation reaches 1.12 so that the normal time is obtained with a total of 924.45 seconds. Continue to calculate the standard time and the results reach 1423.65 seconds with an allowance of 54%. This contributed to an increase in productivity by 5.7%.